Comparison of the head circumference measurement between Down syndrome and normal children - Yahya, Nur Hanis Adibah; Indriyanti, Ratna; Hartanto, Rudy (Padjadjaran Journal of Dentistry, 2012)
Introduction: Growth and development assessment in children is measured by the head circumference measurement or as known as occipital-frontal circumference. In cases of genetic abnormalities such as Down syndrome which is caused by extra chromosome 21, give distinct features in the craniofacial profile, hence the author finds it is useful to observe the changes in their growth, mainly the head circumference. The purpose of this research is to analized comparison between head circumference measurement in children with Down syndrome in Sekolah Luar Biasa-C and normal children, Methods: Type of this research is analytical with surveying technique, using cross sectional studies on 20 children with Down syndrome and 160 normal children 6 to 13 years old. The sample subject. Based on anthropometry landmark on point Glabella to Opisthocranion, measurement is taken using a non-stretchable, flexible measuring tape. Result: There are significant differences between the head circumference of children in both group according to age and gender; except age 6 male, with the mean value of children with Down syndrome compare to normal circumference measurement were smaller 3 to 5 cm behind the normal children in this research. Conclusion: The head circumference of the children with Down syndrome over all from age 6 to 13 years old were smaller than the regular children in same age and same gender.